Perlindungan Hukum Korban Cyberbullying: Kajian atas Peran Media Sosial dan Tanggung Jawab Penyedia Layanan (Neolectura, 2023)
The rapid development of technology nowadays has both positive and negative impacts on society, including the emergence of cyberbullying. Therefore, this research aims to investigate how social media can influence the occurrence of cyberbullying and how the responsibility of service providers can help protect the victims. This research is a normative (doctrinal) study that utilizes data sources such as literature, references, and documents. The research approach used is the statute approach, which analyzes relevant laws and regulations regarding the legal protection of cyberbullying victims. The findings of this research highlight that legal protection and ethical behavior in social media complement each other in creating a safe and fair environment for all users. Existing laws can be applied to address cyberbullying cases, and criminal law reforms are also underway to enhance protection for the victims. Additionally, the responsibility of social media service providers is crucial in safeguarding cyberbullying victims. They should have clear policies, effective reporting mechanisms, and adequate privacy protection. Furthermore, social media users also need to adhere to ethical communication practices to prevent cyberbullying incidents.